2020
DOI: 10.1140/epjds/s13688-020-00228-9
|View full text |Cite
|
Sign up to set email alerts
|

News and the city: understanding online press consumption patterns through mobile data

Abstract: The always increasing mobile connectivity affects every aspect of our daily lives, including how and when we keep ourselves informed and consult news media. By studying mobile web data, provided by one of the major Chilean telecommunication companies, we investigate how different cohorts of the population of Santiago De Chile consume news media content through their smartphones. We address the issue of inequalities in the access to information, trying to understand to what extent socio-demographic factors impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Attributes are highly associated to specific news media consumption patterns. In particular, education and age play a significant role in shaping the consumers behaviour even in the digital context, in agreement with a large body of literature on off-line media distribution channels [12].…”
Section: Condition Of News Writing Learning Media In Unssupporting
confidence: 79%
“…Attributes are highly associated to specific news media consumption patterns. In particular, education and age play a significant role in shaping the consumers behaviour even in the digital context, in agreement with a large body of literature on off-line media distribution channels [12].…”
Section: Condition Of News Writing Learning Media In Unssupporting
confidence: 79%
“…Ucar et al revealed the socioeconomic gap by mobile service consumption [33]. Vilella et al found that education and age play a role in news media consumption patterns in Chile, using a dataset that provides information about the visited websites [34].…”
Section: Introductionmentioning
confidence: 99%
“…In the digital era, the human sleep-wake cycle (SWC) is also studied using infocommunication systems, such as smartphones [39,40], websites [34,41,42], social media [43] and call detail records (CDR) [38,[44][45][46][47][48][49]. Cuttone et al used screen-on events of the smartphones to study the daily sleep periods [39], and Aledavood et al examined the social network of different chronotypes, using the same data set [40].…”
Section: Introductionmentioning
confidence: 99%
“…Rather, it might be related to how less-educated people consume news: for instance, US adults who rely mostly on social media for news tend to have lower levels of education than those who mainly use several other platforms [ 31 ]. Another study in Chile found strong correlations between the socio-demographics of users and online news media content [ 21 ]. Given that polarization and spreading of misinformation is more likely on social media [ 19 ], our results could also be used to identify those populations and areas which could be more susceptible to these problems.…”
Section: Discussionmentioning
confidence: 99%
“…There is qualitative confirmation that mobile digital usage might exacerbate socio-economic inequalities given the impact that social media and online information resources have on the social, political and economic aspects of our society [ 18 , 19 ]. It is also known that time on some social platforms, watching videos or playing videogames [ 20 ] or news media consumption patterns [ 21 ] depend on users' SES, and that students’ performance is related to different patterns in their Internet usage [ 22 , 23 ]. All these studies suggest a significant disparity in how mobile services are consumed, even in developed economies where the technology access gap is not significant.…”
Section: Introductionmentioning
confidence: 99%